In Memoriam of Giovanni Carbonara - Mario Centofanti (Disegnare con)
Giovanni Carbonara was an architect, Emeritus, Professor of Architectural Restoration at “Sapienza Università di Roma”, head of the “Scuola di Specializzazione in Beni Architettonici e del Paesaggio” from 1995 to 2013, memeber of the “Consiglio Superiore per i Beni Culturali e Paesaggistici”, president of the “Comitato tecnico-scientifico per i Beni Architettonici e Paesaggistici del Ministero per i Beni e le Attività Culturali”,  member of the “Comitato nazionale per lo studio e la conservazione dei giardini e dei parchi storici”, memeber of the “Pontificia Insigne Accademia di Belle Arti e Lettere dei Virtuosi al Pantheon”, commissioner member of the “Ministero degli Affari Esteri per la costruzione e il restauro delle ambasciate d’Italia all’estero”, awarded the Gold Medal for “Benemeriti della Cultura e dell’Arte” by the President of the Italian Republic in 2008. He was a leading exponent and reference point of the so called Roman School, and author of fundamental essays on the theory and practice of architectural restoration, with original and foundational contributions in the formulation of the theory of Critical-Conservative Restoration. He has supervised numerous important interventions and consultancies for civil and religious monuments in Italy country and beyond. The Management and Editorial Board of DISEGNARECON, mindful of his cultural support for the journal since its foundation, wish to remember him by reproposing in full English text the editorial published in issue 14 of January 2015, still relevant in terms of the theoretical-methodological approach, focused on to the topic “Design for Restoration: beyond the Survey” edited by Giovanni Carbonara, Mario Centofanti and Roberto Mingucci (https://disegnarecon.univaq.it/ojs/index.php/disegnarecon/article/view/128). The issue of DISEGNARECON 14/2015 also marked, significantly, the shift of DISEGNARECON towards a more properly interdisciplinary connotation.   DOI: https://doi.org/10.20365/disegnarecon.29.2022.aw